Partisipasi Aktif Warga Desa Dalam Memperkuat Kemandirian dan Pemberdayaan Ekonomi Desa Semambung Kecamatan Wonoayu, Sidoarjo: Active Participation of Village Residents in Strengthening Independence and Economic Empowerment of Semambung Village, Wonoayu District, Sidoarjo - Wardah, Zahrotul; Sita Dewi, Aditya; Aji Laksono, Ilham; Anwar, Chairil (TALI JAGAD JOURNAL, 2024)
Community economic empowerment is one of the strategic steps in improving the quality of life and independence of residents, especially in rural areas. Resident participation in this process is very important, because the success of the empowerment program is highly dependent on the active involvement of the community itself. The type of research used is descriptive qualitative triangulation research. In this case, the subject studied was the participation of residents of RT 03 in Semambung Wonoayu village. The research was conducted directly in RT 03, Semambung Wonoayu village. The time of this research was conducted on July 15, 2024 to August 15, 2024. The results of the study showed that residents of RT 03 RW 02 knew the indicators of the winner of RT Mandiri Sejahtera. This can be validated by both residents and administrators who stated that the conclusion of the indicator of the winner of RT Mandiri Sejahtera is that the community is able to solve its problems independently.